PROSES PENGERINGAN CHIP DARI LENJERAN DENGAN METODE AERASI DAN KONDENSASI - Oka Saputra; R. Mursidi; Tamaria Panggabean (Jurnal Teknik Pertanian Sriwijaya, 2012)
This study aims to determine the influence of ambient air temperature which is temperature and RH (relative humidity) in drying process using aeration and condensation method. Aeration method utilized natural air flow from environment to flow hot air from heater chamber to the drying chamber. Condensation method sealed air flow from environment to minimize ambient air temperature and relative humidity inside drying chamber. Parameters observed were evaporated water, drying time, material weight reduced and electrical energy needs. The study showed 12 hours drying process evaporate 1,775 gram water by aeration method while condensation method evaporate 1,788 gram water. Nevertheless to gain 9% water content takes 6 hours 33 minutes by aeration method while condensation method takes 5 hours 33 minutes. It also needs 1.0943KWh electrical energy by aeration method while condensation method needs 1.0159 KWh.Â  Keywords : chip lenjeran, aeration method, condensation method